USE OF SOUND ATTENUATION WITH SONIC CRYSTAL STRUCTURES IN RESIDENTIAL AREAS DUE TO HIGHWAYS - Handayani, Dewi (Journal of Applied Engineering Science, 2023)
Indonesia is a growing nation that needs assistance placing structures beside roadways. Ideally, one should place buildings along residential roads rather than main or collector highways. Due to the high levels of vehicular noise pollution on Indonesian arterial and collector roads, many buildings are located alongside them. This negatively impacts both the environment and human health. As a result, efforts must be made to reduce noise, and one such endeavor is the construction of noise-absorbing structures. Walls are commonplace, noise-absorbing structures with low sound-absorption capacities and fewer aesthetic drawbacks. Sonic crystals are a novel method of noise reduction. This study aims to evaluate the effectiveness of sonic crystals and their possible application in residential areas to reduce noise from the roads. Tests were carried out in an outdoor setting using a real scale. By describing the sonic crystal, it is possible to determine quantitatively how much sound it can absorb. It is also possible to obtain the sound’s shapes that sonic crystals can attenuate. The findings indicate that the maximum IL value is 21.57 dB, and the average IL value is 16.90 dB. The area that the sonic crystal attenuates enough is about 3 meters after the crystal and roughly 2 meters from the crystal’s center axis, respectively. These findings concern using sonic crystals to lessen noise from traffic in residential areas.